2010
DOI: 10.2478/v10038-010-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 12-Week Aerobic Exercises on Rate of Mental Health in Male Students of Ahvaz Payam Noor University

Abstract: Purpose. The purpose of this study was to investigate the effects of 12-week aerobic exercises on self-esteem, social desirability and rate of mental health in male students of Payam Noor University (PNU). Basic procedures. For this reason we used male college students (n = 80, age = 22 ± 2. 1) who did not do any sport. They were randomly assigned to experimental (n = 40) and control (n = 40) groups, after having been selected via stratified random sampling among students of Ahvaz Payam Noor University. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This result can be interpreted to mean that there is a relationship between exercise and increased SE. The results of this study correspond with those of other studies (3,13,(23)(24)(25). Ghaffari et al conducted a study with students in an experimental group before and after regular aerobic exercise and found that the mean SE score increased significantly, from 93.1 ± 8.2 to 111.4 ± 8.1 (P < 0.0001).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result can be interpreted to mean that there is a relationship between exercise and increased SE. The results of this study correspond with those of other studies (3,13,(23)(24)(25). Ghaffari et al conducted a study with students in an experimental group before and after regular aerobic exercise and found that the mean SE score increased significantly, from 93.1 ± 8.2 to 111.4 ± 8.1 (P < 0.0001).…”
Section: Discussionsupporting
confidence: 78%
“…Ferdowsi et al reported a significant difference in terms of self-esteem and mental health between the experimental group and the control group after 12 weeks of aerobic exercises (23). A study by Ekeland et al also resulted in a positive response among participants (3).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is a growing interest in the interventions focusing on increasing physical exercise as a supplementary treatment therapy for this population. Studies indicate that exercise therapy is well perceived, and is associated with improved physical health (Ellis et al , 2007; Ferdowsi et al , 2010; Gorczynski and Faulkner, 2010). In this study, aerobic exercise training showed significant effects on the sub-scales of the physical symptoms of anxiety and insomnia in patients with type 2 diabetes mellitus; however, it had no effect on the sub-scales of social functioning disorder and depression, that was inconsistent with the findings of the study by the Sardar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training, such as aerobic exercises, not only promote the individual’s physical health, but also may influence his/her mental condition. As physical and mental status are generally mutually dependent, reduction in physical abilities may cause a decrease in self-esteem, which is a set of abilities, competence and characteristics that an individual believes he/she owns (Ferdowsi et al , 2010). Guszkowska (2003) showed significant reduction of anxiety and depression following single sessions of exercise.…”
Section: Introductionmentioning
confidence: 99%